2001
DOI: 10.1046/j.1365-4362.2001.01197.x
|View full text |Cite
|
Sign up to set email alerts
|

Type III Ehlers–Danlos syndrome: correlations among clinical signs, ultrasound, and histologic findings in a study of 35 cases

Abstract: The Beighton scoring system, the US findings, and the aspect and diameter of the scars suggested that the disease can be divided into three different stages which allow the correlation, over progressive intervals of values, of the articular hypermobility and atrophic wrinkled scars. Our results showed that US test is able to confirm the clinical diagnosis and to evaluate the seriousness of hypermobile joints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Furthermore, we found that both the classical and the hypermobility types of EDS were accompanied by a reduced thickness of the dermis, which was reliably assessed by 20‐MHz ultrasonography. In a recent study, an analysis of skin thickness in patients with the hypermobility type of EDS performed by 10‐MHz ultrasound showed a decrease in the thickness of the dermis and subcutis together 7 . However, because of the low resolution of 10‐MHz ultrasound, the authors could not attribute this reduction to a specific layer.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, we found that both the classical and the hypermobility types of EDS were accompanied by a reduced thickness of the dermis, which was reliably assessed by 20‐MHz ultrasonography. In a recent study, an analysis of skin thickness in patients with the hypermobility type of EDS performed by 10‐MHz ultrasound showed a decrease in the thickness of the dermis and subcutis together 7 . However, because of the low resolution of 10‐MHz ultrasound, the authors could not attribute this reduction to a specific layer.…”
Section: Discussionmentioning
confidence: 94%
“…There was a difference in joint width for left elbows, but not for right elbows. A number of studies have reported differences between dominant and non-dominant arms 6,18,25,26 . However, the populations of these studies were comprised of overhead throwing athletes whose dominant and non-dominant elbows are placed under significantly different amounts of repetitive stress.…”
Section: Discussionmentioning
confidence: 99%
“…12 The PXE echostructure was also different from that in other connective tissue diseases studied with HFUS and could be used for differential diagnosis in ambiguous cases. Several publications have stated that dermal thickness in classical and hypermobile forms of Ehlers-Danlos syndrome is reduced, [18][19][20] although dermal echogenicity is homogeneous.…”
Section: Discussionmentioning
confidence: 99%